Prediction of Hemophilic Carriers: a New Statistical Approach Using Simultaneous Assays of Factor VIII Coagulant Activity, Factor VIII Related Antigen and Ristocetin Cofactor Activity - Chun-Yet Lian, Eric; Diez-Ewald, María; Walter, Stephen D.; Núñez, Roger; Lian, Jean-Fern; Harkness, Donald R. (Investigación Clínica, 2009)
The posterior probability of each individual for normal or hemophilic carrier was calculated by multivariate discriminant analysis. When both factor VIII coagulant activity and factor VIII-related antigen were used, all of the 30 normal females and 18 of 20 obligatory carriers were correctly classified. When factor VIII coagulant activity and ristocetin cofactor activity were used, 97% of the normal females and 75% of carriers were correctly predicted. When all three parameters were taken into consideration in discriminant analysis, all normals and 17 of 20 carriers were correctly classified. We conclude that concurrent determination of both factor VIII coagulant activity and ristocetin cofactor activity can be used as an alternate or adjunctive method for detecting carriers.